Efficacy and safety profile of calcineurin inhibitor salvage therapy in autoimmune hepatitis. (1st November 2020) - Roberts, Stuart K.; Strasser, Simone I.; Nicoll, Amanda J.; Kemp, William; Majeed, Ammar; Mitchell, Joanne; Stuart, Katherine; Gow, Paul; Sood, Siddharth; MacQuillan, Gerry; George, Jacob; Mitchell, Jonathan; et al.
Abstract: Background: As data is limited on the outcomes of calcineurin inhibitors (CNI) in autoimmune hepatitis (AIH), we evaluated the efficacy and safety of CNI in AIH patients who failed prior treatment(s). Methods: A retrospective study was performed of AIH patients who received cyclosporine A (CsA) and/or tacrolimus (TAC) after prior treatment(s) failure. Records were reviewed for baseline demographic and clinical characteristics, and treatment outcomes. The primary outcome was biochemical remission. Results: Thirty-three AIH patients received CNI across seven liver centers:17 received CsA, 21 TAC and 5 TAC after CsA failure/intolerance. 82% received CNI for an insufficient response to treatment(s). Overall, 48% of CNI treated patients achieved biochemical remission including 41% in prior non-responders and 83% in treatment intolerant patients. Remission rates with CNI as second-line and third-line therapy were 63% and 29% respectively. There were no baseline predictors of response to CNI on multivariate analysis. Eighteen (55%) patients developed significant side effects and 8 (24%) discontinued due to intolerance. Three patients required liver transplantation for decompensated cirrhosis and 6 patients died including one from malignancy possibly related to CNI. Conclusion: CNI salvage therapy is well tolerated and moderately effective achieving remission in around 50% of AIH who failed standard therapy.